Silychristin: Skeletal Alterations and Biological Activities - Biedermann, David; Buchta, Martin; Holečková, Veronika; Sedlák, David; Valentová, Kateřina; Cvačka, Josef; Bednárová, Lucie; Křenková, Alena; Kuzma, Marek; Škuta, Ctibor; Peikerová, Žaneta; Bartůněk, Petr; et al. (Journal of natural products, 2016)
Silychristin is the second most abundant flavonolignan (after silybin) present in the fruits of Silybum marianum. A group of compounds containing silychristin (3) and its derivatives such as 2,3-dehydrosilychristin (4), 2,3-dehydroanhydrosilychristin (5), anhydrosilychristin (6), silyhermin (7), and isosilychristin (8) were studied. Physicochemical data of these compounds acquired at high resolution were compared. The absolute configuration of silyhermin (7) was proposed to be identical to silychristin A (3a) in ring D (10R,11S). The preparation of 2,3-dehydrosilychristin (4) was optimized. The Folin-Ciocalteau reduction and DPPH and ABTS radical scavenging assays revealed silychristin and its analogues to be powerful antioxidants, which were found to be more potent than silybin and 2,3-dehydrosilybin. Compounds 4-6 exhibited inhibition of microsomal lipoperoxidation (IC50 4-6 μM). Moreover, compounds 4-8 were found to be almost noncytotoxic for 10 human cell lines of different histogenetic origins. On the basis of these results, compounds 3-6 are likely responsible for most of the antioxidant properties of silymarin attributed traditionally to silybin (silibinin).
Keywords: Plant Extracts; Antioxidants; ostropestřec mariánský; kořeny rostlin; Fruit; Humans; Molecular Structure; Silymarin; silibinin; molekulární struktura; Silybin; lidé; antioxidancia; rostlinné extrakty; Plant Roots; ovoce; silymarin; Silybum marianum